Al-Taftāzānī’s Refutation of Akbarian Metaphysics and the Identification of Absolute Being with the Necessary Being: Introduction, Translation and Critical Commentary on Commentary of the Objectives 2.1.2 - Ansari, Rosabel (Oriens, 2022)
This article discusses the Ašʿarī theologian Saʿd al-Dīn al-Taftāzānī’s (d. 793/1390) refutation of Akbarian metaphysics and the identification of absolute being (al-wuǧūd al-muṭlaq) with the Necessary Being, i.e. God, in his summa Šarḥ al-Maqāṣid. Al-Taftāzānī argues that the Akbarians are amateur philosophers who misappropriated the philosophical tradition. If absolute being were identified with God, we would not be able to say that anything else is, leading to monism. Instead al-Taftāzānī argues that absolute being is a mind-dependent concept. Al-Taftāzānī’s refutation reveals the contested nature of the Avicennan legacy and the important role of the Akbarian school in its development.